No More Sunburn - Reble, Carina; Meinke, Martina; Rass, Jens (Optik & Photonik (Internet), 2018)
A UV‐LED based system was developed that allows to determine the sun protection factor (SPF) of sunscreen lotions in a non‐invasive way in vivo. This method is faster and reduces the medical risk for the test subjects